Estimating Exploitation and Modeling the Effects of Hand Fishing on a Flathead Catfish Population in East Texas. (10th November 2016) - Bodine, Kristopher A.; Schlechte, J. Warren; Ott, Richard A.; Bennett, Daniel L.; Norman, Jacob D.
Abstract: The recent legalization of hand fishing in Texas has prompted concern for the potential overharvest of catfish. Large (≥600 mm) Flathead Catfish Pylodictis olivaris are thought to be vulnerable to this angling method, and the potential effects of selectively harvesting large fish are not well understood. Therefore, in April 2013 we quantified size‐ and gear‐specific exploitation of Flathead Catfish in Lake Palestine, Texas, by tagging 255 fish within three size‐groups (457–599, 600–761, and ≥762 mm) with reward tags. We also quantified abundance, mortality (total and natural), and growth to simulate the effects of exploitation (particularly of size‐groups targeted by hand fishing) on the Flathead Catfish population. Exploitation was low (3.2%), and size‐specific harvest was less than 5% for all size‐groups. Trotlines and hand fishing accounted for 100% of observed harvest (50% for each gear). Our models indicated that maximum sustainable yield would be achieved at 10% to 15% exploitation. Recruitment overfishing and growth overfishing were evident at about 15% to 20% exploitation. When we simulated increased exploitation by hand fishers only (achieved by only increasing exploitation of fish ≥762 mm), recruitment overfishing was not evident until 55% exploitation, and growth overfishing never occurred. These results indicate that the current low harvest by hand fishers will have little impact on yield or size structure of Flathead Catfish, and, in most scenarios, the current 457‐mm minimum length limit can maintain a sustainable fishery. Undoubtedly, any additional harvest of trophy fish (≥762 mm) will reduce trophy fish abundance; however, exploitation of trophy fish (alone) would need to exceed 55% before populations become unsustainable. Received February 9, 2016; accepted June 29, 2016 Published online November 10, 2016